The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13643-020-01540-1
|View full text |Cite
|
Sign up to set email alerts
|

FLT3 inhibitors in acute myeloid leukaemia: assessment of clinical effectiveness, adverse events and future research—a systematic review and meta-analysis

Abstract: Background FMS-like tyrosine kinase 3 (FLT3) is the most frequent mutation in AML. With two FLT3 inhibitors recently approved by the FDA (midostaurin and gilteritinib), there is a need to evaluate these targeted agents. Purpose To assess the clinical effectiveness of FLT3 inhibitors in AML patients. Methods Standard systematic review methods were utilised. Searches were conducted to July 2020 for completed and in-progress randomised controlled trials of FLT3 inhibitors in AML. A fixed-effect meta-analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Several recent reviews have summarized the evolving FLT3 landscape and identified important unanswered questions. [151][152][153] Additional tyrosine kinase inhibitors are being studied for targets other than FLT3 and are in various stages of development, as recently described. 154…”
Section: Clonal Hematopoiesis and Therapy Related Myelodysplastic Syndrome And Amlmentioning
confidence: 99%
“…Several recent reviews have summarized the evolving FLT3 landscape and identified important unanswered questions. [151][152][153] Additional tyrosine kinase inhibitors are being studied for targets other than FLT3 and are in various stages of development, as recently described. 154…”
Section: Clonal Hematopoiesis and Therapy Related Myelodysplastic Syndrome And Amlmentioning
confidence: 99%
“…The membrane-bound FMS-like tyrosine kinase-3 (FLT3) is activated by the FLT3 ligand and contributes to the development of hematopoietic cells. FLT3 is encoded on chromosome 13q12.2 and consists of five extracellular, immunoglobulin-like domains, a transmembrane domain, a juxtamembrane domain, and an intracellular tyrosine kinase domain (Majothi et al 2020 ; Marensi et al 2021 ; Scholl et al 2020 ). Mutations in FLT3 promote cell growth and chemoresistance and lead to AML with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in FLT3 promote cell growth and chemoresistance and lead to AML with poor prognosis. Internal tandem duplications in FLT3 (FLT3-ITD) occur in 20–35% of patients with de novo AML and tyrosine kinase domain (FLT3-TKD) mutations occur in 5–10% of patients with de novo AML (Heidel et al 2006 ; Majothi et al 2020 ; Marensi et al 2021 ; Scholl et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…FLT3 is another highly attractive therapeutic target, due to the fact it is overexpressed in most AML cases with a high mutational rate [16,17]. Proven effects on tumor cell cycling by FLT3 inhibitors [18][19][20] have led to many clinical trials either as a monotherapy, or as combinatorial therapy with conventional chemotherapy, with early meta-analysis suggesting a statistically significant 17% improvement in survival [21].…”
Section: Introductionmentioning
confidence: 99%